The Effect of Storytelling Method through Fairy Tale Book Media on Children's Knowledge and Attitudes about Fruit And Vegetable Consumption - Alfina, Tiara Yulie; Sumaryono, Dino; Ismiati (Media Gizi Indonesia, 2024)
In Indonesia, fruit and vegetable consumption is still low, especially among school-age children. culture, environment, socioeconomic, and ethnic background are factors that influence vegetable consumption. Education can help improve children's knowledge and perceptions about fruit and vegetable consumption. This research aims to determine the effect of the storytelling method through fairy tale books on children's knowledge and attitudes regarding fruit and vegetable consumption in MIN 2 Bengkulu City. This research shows that fairy tale book media intervention students' knowledge and attitude showed significant effect with p-value <  0.001. So that it can be concluded that storytelling method through fairy tale book media can be an alternative learning method in the classroom to increase children awareness, knowledge, and attitudes about the importance of consuming and vegetables.